Методи штучного інтелекту для оптимізації вимірювань масової витрати рідини - Бяллович, Д. Ю. (ХНУРЕ, 2025)
In modern industrial processes, accurate measurement of fluid mass flow is critically important for efficient resource management and increased productivity. Traditional measurement methods have limitations in terms of accuracy, adaptability to different operating conditions, and real-time data processing. The use of artificial intelligence (AI) methods enhances measurement accuracy, reduces errors, and optimizes costs for sensor systems, offering new approaches to improving the accuracy, reliability, and efficiency of fluid mass flow measurements. This study examines the main AI methods used to optimize fluid mass flow measurements, their advantages, and development prospects.
Keywords: вимірювання масової витрати рідини; витрата рідини